2020
DOI: 10.1007/s00216-020-02776-5
|View full text |Cite
|
Sign up to set email alerts
|

Double bond localization in unsaturated rhamnolipid precursors 3-(3-hydroxyalkanoyloxy)alkanoic acids by liquid chromatography–mass spectrometry applying online Paternò–Büchi reaction

Abstract: Lipids are biomolecules with a broad variety of chemical structures, which renders them essential not only for various biological functions but also interestingly for biotechnological applications. Rhamnolipids are microbial glycolipids with surface-active properties and are widely used biosurfactants. They are composed of one or two L-rhamnoses and up to three hydroxy fatty acids. Their biosynthetic precursors are 3-hydroxy(alkanoyloxy)alkanoic acids (HAAs). The latter are also present in cell supernatants as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 80 publications
(94 reference statements)
1
11
0
Order By: Relevance
“…Because BzPy attachment was observed for unsaturated and saturated lipids, BzPy most likely also reacts with the head group, in a reaction other than PB functionalization, or attaches to lipids in a noncovalent manner. This is also consistent with the reports by Xia31 and Hayen30 about PB reaction by-products in in-solution reactions. The numbers of lipids with or without BzPy attachment are compared in Figure3.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Because BzPy attachment was observed for unsaturated and saturated lipids, BzPy most likely also reacts with the head group, in a reaction other than PB functionalization, or attaches to lipids in a noncovalent manner. This is also consistent with the reports by Xia31 and Hayen30 about PB reaction by-products in in-solution reactions. The numbers of lipids with or without BzPy attachment are compared in Figure3.…”
supporting
confidence: 93%
“…24−28 The latter functionalization scheme, pioneered by Ma and Xia, 29 has been used by numerous groups to assign DB positions in direct infusion and LC−MS workflows. 30,31 Lipid DB isomer assignment from surfaces or local alterations of lipid isomer abundances in tissues, however, require desorption-based ionization methods. 14,20,23,32 33,34 In one of our recent studies, we identified benzophenone (BPh) as a compound that can act as a MALDI matrix and reacts with lipids in a PB reaction during laser irradiation, a process termed PB-reactive MALDI.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the discovery by Ma and Xia [114] that light-induced Paternò-Büchi (PB) reactions can aid DB position assignments with relative ease and with inexpensive equipment has sparked the interest in chemical derivatization strategies that enable structure elucidation. In particular, most recent derivatization strategies target lipid DBs or adjacent carbon atoms and are based on PB [114][115][116][117][118][119][120][121][122], epoxidation [123][124][125], ozonolysis [126], or hydroxylation reactions [127] (Scheme 2).…”
Section: Chemical Derivatization Prior To Tandem Msmentioning
confidence: 99%
“…PB reactions with acpy and other carbonyl compounds have been used not only to analyze standards but also to investigate complex lipid extracts from body fluids, cells, or tissues revealing DB positions and sometimes sn-isomers for CEs [116,130], FAs [116], GPs [121], and SLs [131]. Recently, PB methods have been extended to also target small FA metabolites [117][118][119] or have been adapted to benefit other advanced tandem MS tools such as UVPD [115] or ion/ion reactions [122].…”
Section: Chemical Derivatization Prior To Tandem Msmentioning
confidence: 99%
“…[24][25][26][27][28] The latter functionalization scheme, pioneered by Ma and Xia, 29 has been used by numerous groups to assign DB positions in direct infusion and LC-MS workflows. 30,31 Lipid DB isomer assignment from surfaces or local alterations of lipid isomer abundances in tissue, however, require desorption-based ionization methods. 14,23,20,32 For example, MALDI MS and MS imaging (MSI) tools were developed that enable pinpointing lipid DB positions.…”
Section: Introductionmentioning
confidence: 99%